Sistem Informasi Penerimaan Peserta Didik Baru Online pada SMK Nasional Pati - Evanita; Maulana Wijayanto (STEKOM PRESS, 2021)
Fieldwork Practices were carried out at Pati National Vocational High School, from January 25, 2021 to February 20, 2021. In this Fieldwork Practice, the authors created an efficient application and management system for student data, especially for new students in a computerized manner. By using this web-based programming system, it can simplify data collection, automatic ranking based on National Exam scores, reduce paper usage, reduce cheating and are expected to overcome the obstacles experienced by both the committee for admission of new students and the parents of the students themselves. . This research produces a system that can handle the admission process of new students with the hope that it is more efficient and effective than the previous method.